2006
DOI: 10.1002/cne.21176
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationship between synapse loss and β‐amyloid deposition in Tg2576 mice

Abstract: Although there is evidence that β-amyloid impairs synaptic function, the relationship between β-amyloid and synapse loss is not well understood. In this study, we assessed synapse density within the hippocampus and the entorhinal cortex of Tg2576 mice at 6-18 months of age using stereological methods at both the light and electron microscope levels. Under light microscopy, we failed to find overall decreases in the density of synaptophysin-positive boutons in any brain areas selected, but bouton density was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
96
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 86 publications
(75 reference statements)
14
96
1
Order By: Relevance
“…4C-E) results demonstrated that the decrease in PKC protein level in the hippocampal CA1 area of Tg2576 mice was the result of the decreased numbers of presynaptic boutons that contained PKC rather than a result of decreased PKC levels in the individual boutons. A previous study, for another example, demonstrated that the number of total synapses was not changed in CA1 stratum radiatum (Dong et al, 2007), whereas our results demonstrate a significant decrease in the synapses per unit volume of CA1 stratum radiatum.…”
Section: Discussioncontrasting
confidence: 91%
“…4C-E) results demonstrated that the decrease in PKC protein level in the hippocampal CA1 area of Tg2576 mice was the result of the decreased numbers of presynaptic boutons that contained PKC rather than a result of decreased PKC levels in the individual boutons. A previous study, for another example, demonstrated that the number of total synapses was not changed in CA1 stratum radiatum (Dong et al, 2007), whereas our results demonstrate a significant decrease in the synapses per unit volume of CA1 stratum radiatum.…”
Section: Discussioncontrasting
confidence: 91%
“…Accumulating evidence points to the in vivo toxicity of compact amyloid plaques. Dong et al (22) observed a selective loss of dendritic synapses occurring in the proximity of amyloid plaques in the entorhinal cortex and the outer molecular layer of the dentate gyrus of aged Tg2576 mice (22). Indeed, amyloid plaques are selectively associated with dystrophic neurites in these mice (23), and such deposits have been associated with local structural disruption of synapses and breakage of neuronal branches (24).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular layer of the dentate gyrus is one of the first regions to show amyloid deposition and synapse loss in the Tg2576 mouse model of AD (Su and Ni, 1998;Reilly et al, 2003;Dong et al, 2007). However, it is difficult to know the implications of increases in synapse density after memantine administration in Tg2576 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerating axons were identified on photographs by the presence of vesicular and lamellar debris within the atrophic axon. A stereological dissector technique was used to measure the density of synapses and degenerating axons (West and Gundersen, 1990;Geinisman et al, 2000;Dong et al, 2007). Each dissector consisted of micrographs of two adjacent ultrathin sections, a reference section and a look-up section immediately above it.…”
Section: Quantitative Evaluation Of Synapse Density and Axon Morphologymentioning
confidence: 99%